Vaccine hesitancy and self-vaccination behaviors among nurses in southeastern France. Issue 5 (29th January 2020) - Wilson, Rose; Zaytseva, Anna; Bocquier, Aurélie; Nokri, Amale; Fressard, Lisa; Chamboredon, Patrick; Carbonaro, Christian; Bernardi, Stéphane; Dubé, Eve; Verger, Pierre
Highlights: Nurses in France will soon play a more important role in vaccinating the population. Their self-reported uptake of recommended vaccines is far below official objectives. More than 40% of nurses were vaccine hesitant, with community nurses less so. Nurses' hesitancy mainly focused on seasonal flu, hepatitis B, and HPV vaccines. Nurses share some of the public's doubts about vaccine safety and benefits. Abstract: Background: Health care worker vaccine uptake rates are below official targets, and studies demonstrate some are vaccine hesitant. We assessed self-vaccination behavior, vaccine hesitancy (VH), and associated factors in a representative sample of nurses. Methods: Cross-sectional questionnaire survey in 2017–18 in southeastern France (5 million inhabitants): community nurses were randomly selected from a list provided by the Inter-Regional Nurses' Council (stratified by gender and district of practice) and interviewed by telephone. Because no such list exists for hospital nurses (74% of all nurses in southeastern France), we randomly selected hospitals, taking their size into account and stratifying by district. Hospital nurses practicing in medicine, surgery, obstetrics, and gynecology departments and present at the time of the survey were included and interviewed face-to face. We measured VH according to the WHO definition (refusal, delay, or acceptance with doubts about at least one vaccine). Interviewers administered the questionnaires. We used multivariable logistic regression to analyze potential associations between VH, vaccine risk perceptions and trust in health authorities. Results: Interviews were completed with 1539 nurses (response rate: 85%). Self-reported vaccine coverage ranged from 27% (seasonal influenza vaccine, recommended, 2016/17 season) to 96% (Bacillus Calmette–Guérin vaccine, mandatory). The VH prevalence rate was 44% (95% confidence interval: 38.7–48.4) and most often concerned seasonal influenza or A(H1N1) vaccines (54%) and the hepatitis B vaccine (18%). VH was significantly more frequent among nurses with low trust in health authorities or high vaccine risk perceptions. Conclusion: Nurses in southeastern France have low levels of self-vaccination acceptance for most recommended vaccines. In addition, they have a high VH prevalence focused on the same vaccines as among the general population. These are important findings given that nurses are in regular contact with patients vulnerable to vaccine-preventable diseases and their VH could negatively influence patients' vaccination acceptance.